EFEKTIVITAS KAMPANYE EDUKASI PT SINERGI BICARA INDONESIA DALAM MENINGKATKAN KOMPETENSI PUBLIC SPEAKING KOMUNITAS TEMAN BICARA - Wati, Lily Rahma; Akhyar, Taufik; Farid, Muhammad Mifta (Universitas Islam Syekh Yusuf, 2024)
This study aims to analyze the effectiveness of an educational campaign organized by PT Sinergi Bicara Indonesia in improving the public speaking competence of Teman Bicara Community members. Public speaking is an important skill in many aspects of life, both professional and social. Therefore, educational programs designed to improve this skill need to be evaluated to understand their impact on audiences. This study uses a quantitative approach with data collection methods through questionnaires distributed to 100 respondents. The results showed a positive and significant relationship between participation in the educational campaign and the improvement of effective communication skills, particularly in public speaking. The training program used interactive methods as well as hands-on practice, which proved to have a significant impact in increasing the audience's confidence and speaking ability in various situations. The findings confirm that educational campaigns in the form of public speaking training programs have an important role in developing communication skills that are relevant for professional and social needs. Therefore, more educational programs are needed that provide not only theory, but also hands-on experience so that participants can be more confident and skilled in public speaking.